Chinese-German Relations and the Fourth Taiwan Strait Crisis - Marian Ehret; Mohd Azizuddin Mohd Sani; Mohammad Zaki Ahmad (Contemporary Chinese Political Economy and Strategic Relations: An International Journal, 2023)
The purpose of this study was to understand the effect of the Fourth Taiwan Strait Crisis in 2022 and 2023 on Chinese–German relations. American–German relations were considered as the most important variable impacting relations between Beijing and Berlin. A methodological media content analysis, using context coding, was used to arrive at findings and discussion. An unstructured interview with an expert on media studies confirmed essentially the findings of the media content analysis. An integrated literature review on the American–German conflict indicated a contribution of the Crisis’s long-term effects to an essential, economic weakening of Germany in the years to come. Another Trump administration could deliver this outcome. Ultimately, the strategic partnership between China and Germany could end. German interaction with Beijing would politically be aligned with American interests. Control over Germany, Europe, the West, and world domination could be delivered to the United States. China and Russia would probably remain independent.